GreenRx Initiative : educating on responsible medication disposal / Muhammad ‘Izzuddin Zamery - Zamery, Muhammad ‘Izzuddin (Faculty of Pharmacy, 2023)
The issue of environmental pollution, particularly water pollution due to the improper disposal of toxic substances like medications, has become a pressing concern requiring urgent attention. The GreenRx Initiative aims to address this issue at its core by raising awareness and educating the public. The overarching goal is to encourage responsible medication disposal practices, ultimately preventing environmental damage, especially water pollution resulting from the inappropriate disposal of chemical medications. This campaign will be implemented in collaboration with the District Health Office (PKD) of Kuala Selangor and will target the residents in the surrounding areas. The participants are not only from the general public but also include vulnerable groups such as people with visual impairments who often miss out on the benefits of such programs due to the unsuitability of campaign materials and modules.